Analisis Faktor-Faktor yang Mempengaruhi Minat Belajar Siswa Kelas X TKJ 1 pada Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan (PJOK) di SMK Negeri 3 Selong - Afrijal Rijaya Lulhiah; Tamim, Muhammad Husni; Edy Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning interest is one of the essential factors influencing the success of the learning process, particularly in Physical Education, Sports, and Health (PJOK). A high level of learning interest encourages students to participate actively in learning activities, enhances learning motivation, and supports the achievement of optimal learning outcomes. This study aimed to analyze the internal and external factors influencing the learning interest of Class X TKJ 1 students in PJOK learning at SMK Negeri 3 Selong. This research employed a descriptive quantitative approach. The population consisted of 36 students of Class X TKJ 1 at SMK Negeri 3 Selong, while the sample comprised 26 students selected using a simple random sampling technique. Data were collected through a Google Forms-based questionnaire developed according to indicators of internal and external factors affecting students' learning interest. The data were analyzed using descriptive statistics, including mean scores, percentages, and category analysis. The findings revealed that students' learning interest in PJOK was in the high category. The most dominant internal factor was students' interest in sports activities, with a mean score of 4.50, while the most dominant external factor was the teacher's teaching method, particularly the teacher's ability to provide equal opportunities for all students to participate actively in the learning process, with a mean score of 4.62. These findings indicate that effective teaching methods, peer support, a conducive learning environment, and students' interest in sports activities play significant roles in enhancing students' learning interest in PJOK. The results of this study are expected to serve as a reference for teachers and schools in developing more effective, innovative, engaging, and student-centered learning strategies.